Impacts of microplastics on immunity - Yang, Wenjie; Jannatun, Nahar; Zeng, Yanqiao; Liu, Tinghao; Zhang, Guofang; Chen, Chunying; Li, Yang (Frontiers in Toxicology, 2022)
Most disposable plastic products are degraded slowly in the natural environment and continually turned to microplastics (MPs) and nanoplastics (NPs), posing additional environmental hazards. The toxicological assessment of MPs for marine organisms and mammals has been reported. Thus, there is an urgent need to be aware of the harm of MPs to the human immune system and more studies about immunological assessments. This review focuses on how MPs are produced and how they may interact with the environment and our body, particularly their immune responses and immunotoxicity. MPs can be taken up by cells, thus disrupting the intracellular signaling pathways, altering the immune homeostasis and finally causing damage to tissues and organs. The generation of ROS is the mainly toxicological mechanisms after MP exposure, which may further induce the production of danger-associated molecular patterns (DAMPs) and associate with the processes of toll-like receptors (TLRs) disruption, cytokine production, and inflammatory responses in immune cells. MPs effectively interact with cell membranes or intracellular proteins to form a protein-corona, and combine with external pollutants, chemicals, and pathogens to induce greater toxicity and strong adverse effects. A comprehensive research on the immunotoxicity effects and mechanisms of MPs, including various chemical compositions, shapes, sizes, combined exposure and concentrations, is worth to be studied. Therefore, it is urgently needed to further elucidate the immunological hazards and risks of humans that exposed to MPs.